Stress measurement among charge nurses: developing a cross‐cultural tool. (4th November 2015) - Admi, Hanna; Eilon, Yael; Renker, Paula; Unhasuta, Krongdai
Abstract: Aim: The aim of this study was to develop a cross‐cultural tool for the measurement of stress among charge nurses in general hospitals. Background: Studies of the specific stressors unique to different nursing roles are few, particularly those related to hospital charge nurses. The Charge Nurse Stress Questionnaire is a well‐validated Israeli‐developed scale. However, it has not been tested cross‐culturally. Design: A descriptive methodological study was conducted in Israel, Ohio and Thailand. Method: A total of 2616 nurses from 23 hospitals (small to large size) completed the questionnaire between 2011–2013. The questionnaire was translated into English and Thai. To establish tool validity and reliability, content validity, internal consistency reliability, exploratory and confirmatory factor analysis were performed. Results: Analyses resulted in a final abbreviated version of the questionnaire with 25 items and four stress subscales. Internal consistency for the subscales indicated very good internal consistency. Conclusions: We developed a self‐reported, cross‐cultural, valid and reliable tool for evaluating the specific stressors of the role of charge nurses. A rigorous assessment of charge nurse stress provides a good basis for planning tailored stress reduction interventions. It is recommended to further use the tool in different settings across different countries.